PENGARUH METODE CRITICAL INCIDENT TERHADAP HASIL BELAJAR MENULIS KARANGAN SISWA KELAS V SDN 9 SUMANGA KEC. LIUKANG TANGAYA KABUPATEN PANGKAJENE KEPULAUAN - Fitriyani, Fitriyani; Haslinda Haslinda; Rahmatiah Rahmatiah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of using the Critical Incident active learning strategy on the learning outcomes of writing essays. This research was conducted at SD Negri 9 Sumanga. The population in this study were fifth grade students at SD Negri 9 Sumanga for the 2023/2024 academic year, which consisted of one class. The sampling technique in this study used the total side technique. The subjects in this study were fifth grade students consisting of 27 people, namely 10 boys and 17 girls. The research method used was an experiment with a one group pretest posttest research design.The results of this study based on calculations with 26 degrees of freedom, obtained t count = 5.0144 and t table = 2.056. The results of these calculations show that t count ≥ t table (5.0144 ≥ 2.056). So it can be concluded that there is an effect of using critical incident active learning strategies on the learning outcomes of fifth grade students at SD Negri 9 Sumanga, Liukang Tangaya District, Kab. Pangkajene and Islands.